Ketahanan Bakteri Psikotrofik dari Produk Perikanan Segar terhadap Bakteriosin - Amir Husni; Iwan Y.B. Lelana; Endang Sri Rahayu (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2001)
Fresh fishery products are highly perishable and susceptible to spoilage caused by rapid growth and activity of bacteria. Psychotropic bacteria are the major microorganisms responsible for spoilage when these products stored in ice or under refrigeration. The purposes of this study were to isolate psychrotrophic bacteria from fresh fishery products and to evaluate its resistance to bacteriocins. Fresh fishery products (kembung fish, shrimp, shellfish) samples were obtained from Demangan and Kranggan traditional market. Colony count methods were used to enumerate bacteria, whereas isolation and identification of bacteria was performed by the identification method of Lahallec and Colin (1995). The identification conducted were covering Gram staining and cell morphological examintaion (cell form), motilitym presence or absence of an oxidise, mode of glucose utilization, and capacity for glucose or lactose fermentation, H2S production, and gas production. The resistance assyas by bacteriocin were carried out using agar diffusion method. Seventeen isolates were found abd they were classified as Pseudomonas, Xanthomonas, and Flavobacterium/ Cytophaga. The results show that psychrotropic bacteria resistance to supernatant of lactic acid bacteria and nisin.